Atributos ecossistêmicos e abordagem de comunidades : explorando padrões espaciais e temporais para reservatórios neotropicais. - Gubiani, Éder André (2007)
This study evaluated the spatial and temporal variations in the fish assemblages in Neotropical reservoirs through use of two different approaches: ecosystem approach, using software Ecopath and communities approach through their attributes. Therefore, we used data collected in 30 reservoirs of the Paraná State in 2001. Thirty ecosystem models were generated, one for each reservoir, besides, they were appraised the species richness, diversity index and eveness and at the end that two approaches were appraised in way divergent or convergent. This study was divided into two chapters, the first, entitled "Trophic models in Neotropical reservoirs" in which to evaluate food webs in 30 reservoirs of the Paraná State, Brazil, standardized models (same compartments) were built for every one of them, based on biomass and energy flow, using the software Ecopath. In the second chapter entitled " Ecosystems attributes and communities approach: exploring spatial and temporal patterns for Neotropical reservoirs ". The purpose of this study was to characterize thirty reservoirs located within the Paraná State in six hydrological basins, using some assemblage and ecosystem attributes, as well as the relationship among them. In order to verify those two approaches converges or they diverge in relation to reservoirs.